Comparing Drug Images and Repurposing Drugs with BioGPS and FLAPdock: The Thymidylate Synthase Case. (12th July 2016) - Siragusa, Lydia; Luciani, Rosaria; Borsari, Chiara; Ferrari, Stefania; Costi, Maria Paola; Cruciani, Gabriele; Spyrakis, Francesca
Abstract: Repurposing and repositioning drugs has become a frequently pursued and successful strategy in the current era, as new chemical entities are increasingly difficult to find and get approved. Herein we report an integrated BioGPS/FLAPdock pipeline for rapid and effective off‐target identification and drug repurposing. Our method is based on the structural and chemical properties of protein binding sites, that is, the ligand image, encoded in the GRID molecular interaction fields (MIFs). Protein similarity is disclosed through the BioGPS algorithm by measuring the pockets' overlap according to which pockets are clustered. Co‐crystallized and known ligands can be cross‐docked among similar targets, selected for subsequent in vitro binding experiments, and possibly improved for inhibitory potency. We used human thymidylate synthase (TS) as a test case and searched the entire RCSB Protein Data Bank (PDB) for similar target pockets. We chose casein kinase IIα as a control and tested a series of its inhibitors against the TS template. Ellagic acid and apigenin were identified as TS inhibitors, and various flavonoids were selected and synthesized in a second‐round selection. The compounds were demonstrated to be active in the low‐micromolar range. Abstract : The TS test case : We describe the integrated and innovative BioGPS/FLAPdock pipeline for rapid and effective comparison of protein cavities, off‐target identification, and drug repurposing. Structural, chemical, and energetic properties of the cavities are simply encoded in the corresponding GRID molecular interaction fields. BioGPS discloses pocket similarity, and cross‐docking experiments identify drugs for potential repurposing.